1988
DOI: 10.1177/026624268800600403
|View full text |Cite
|
Sign up to set email alerts
|

The Charcteristics of Expatriate Entrepreneurs

Abstract: DAVID R. BEFUS is with Azusa Pacific University, California, USA, George S. Vozikis is with Memphis State University, Tennessee, USA, and Timothy S. Mescon and Debbie L. Mescon are with Salisbury State University, Maryland, USA. The investment activity of expatriate entrepreneurs in Honduras in Central America and their personal characteristics were compared with other entrepreneurial propulations for this paper. The economic development impact of the expatriate investor was also explored. The profile generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…scenery for painting or walking holidays, redundant property for conversion, and low assembly costs for manufacturing). Our findings provide support for Befus et al (1988), who found US and German expatriate entrepreneurs in central America to be typically individuals who spotted specific opportunities -'mainly because they were expatriates' (Befus et al: 42) -in areas where their skills, knowledge and contacts gave them a competitive advantage over local businesses. This observation aligns with views that in-migrants to rural environments may more readily recognize and respond to certain market opportunities than indigenous residents (Anderson 2000, Smallbone et al 2002, McCain 2003.…”
Section: Motivation To Start-upsupporting
confidence: 80%
See 2 more Smart Citations
“…scenery for painting or walking holidays, redundant property for conversion, and low assembly costs for manufacturing). Our findings provide support for Befus et al (1988), who found US and German expatriate entrepreneurs in central America to be typically individuals who spotted specific opportunities -'mainly because they were expatriates' (Befus et al: 42) -in areas where their skills, knowledge and contacts gave them a competitive advantage over local businesses. This observation aligns with views that in-migrants to rural environments may more readily recognize and respond to certain market opportunities than indigenous residents (Anderson 2000, Smallbone et al 2002, McCain 2003.…”
Section: Motivation To Start-upsupporting
confidence: 80%
“…As suggested by previous work (Befus et al 1988, Lardie´s 1999, SEEs are slow to set themselves up in business following arrival, the average gap being over three years. The delay was even higher for Spanish-based SEEs, where fewer than one-third started up within 12 months, and one in three took three years or more.…”
Section: Start-up Processesmentioning
confidence: 69%
See 1 more Smart Citation
“…Their choice of enterprise varies and, while many work within tourism or providing services for other migrants, the advances in communications technology make the possibilities endless. Importantly, these lifestyle migrants use their businesses as a means to an end; they use them to fund their new lifestyles (Befus et al, 1988;Madden, 1999;Stone and Stubbs, 2007). For example, when small business owners on the Costa del Sol were asked why they moved, they listed climate, quality of life, and lifestyle ahead of business opportunities.…”
Section: The Search For a Better Way Of Lifementioning
confidence: 99%